ohdm 2019
DOI: 10.35248/2247-2452.19.18.1063
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health?Neglected Area on Global Health Map

Abstract: Oral health is an important international public health issue; impacting individuals, communities, health systems, economies and society at large. More importantly, it is one of the most neglected areas on global health map to the current understanding on the mechanism of initiation and progression of oral disease; there are still certain lacunae present in our knowledge of prevention of periodontal disease. In spite of vast understanding of the disease, the inability to identify high-risk forms exists. Preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Oral care and oral health are essential symptoms for many cancers 1,46 and recommended to see a dentist regarding managing oral health symptoms 46 . Changes in taste and taste disorders have been linked with changes in saliva production, dry mouth, and xerostomia 47 . Drinking more fluids may help to improve salivary flow rate and dry mouth symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral care and oral health are essential symptoms for many cancers 1,46 and recommended to see a dentist regarding managing oral health symptoms 46 . Changes in taste and taste disorders have been linked with changes in saliva production, dry mouth, and xerostomia 47 . Drinking more fluids may help to improve salivary flow rate and dry mouth symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking more fluids may help to improve salivary flow rate and dry mouth symptoms. Thus, this strategy may improve taste function 47 . Further, it's been reported that doing oral evaluations before beginning cancer treatments could identify oral infections, fractured teeth or restorations, and periodontal diseases, which could contribute to oral complications upon cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the commonly neglected health issues globally is oral health, and the impact of oral diseases has significant effects on individuals, communities and global health care systems. 1 The evolution of professional health care education over the years is yet to compete with the demographical challenges and inequalities faced, which causes a burden on the system to fight the disease spread, and utilize the scientific knowledge and advanced technology with increasing complexity in the system. In addition to this, there is existing gap in imparting training to medical professionals about importance of oral health and its impact on general health.…”
Section: Introductionmentioning
confidence: 99%